2012
DOI: 10.1080/15321819.2011.600402
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ3 IMMUNOASSAY STANDARDIZATION: COMPARISON OF NIBSC REFERENCE PREPARATION CODE 98/608 WITH AVOTERMIN LOT 205-0505-005

Abstract: Juvista™ drug product contains human recombinant active transforming growth factor beta 3 (TGFβ3; avotermin). Juvista is being developed for the prevention and reduction of human scarring. Phase II and III clinical and development batches of Juvista were assayed for content by an immunoenzymometric assay (IEMA) using a National Institute for Biological Standards and Control (NIBSC) TGFβ3 reference material (98/608) and avotermin standard (Lot 205-0505-005). Paired Juvista TGFβ3 data were compared directly, poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Phase I and II clinical studies of recombinant human TGF-β3 (Avotermin or Juvista) have been successful, where the administration of TGF-β3 reduced scars [82,83]. However, phase III failed and, among other things, the correct system of standardization of the amount of active substance in the sample during the production process was missed [84].…”
Section: Dermal Cells Participating In Different Modes Of Wound Hementioning
confidence: 99%
“…Phase I and II clinical studies of recombinant human TGF-β3 (Avotermin or Juvista) have been successful, where the administration of TGF-β3 reduced scars [82,83]. However, phase III failed and, among other things, the correct system of standardization of the amount of active substance in the sample during the production process was missed [84].…”
Section: Dermal Cells Participating In Different Modes Of Wound Hementioning
confidence: 99%
“…Second, although some approaches have been shown to improve scar appearance, to date there is no available therapy that supports true regeneration of skin with secondary dermal elements. Agents targeting the TGFβ signaling pathway and various cellular treatments using autologous adipose- and bone marrow-derived stem cells showed promise in preclinical trials but have not demonstrated clinical efficacy (So et al, 2011; Little et al, 2012). Considering the physiologic and pathologic role that mechanical forces play in wound healing and scar remodeling (Akaishi et al, 2008; Ogawa et al, 2012; Huang et al, 2017).…”
Section: Current Therapies For Scarringmentioning
confidence: 99%
“…162 Unfortunately, avotermin failed to show efficacy in Phase III trials, possibly due to the use of a different TGF-b3 standard, which led to a twofold overestimation of TGF-b3 concentration, and, therefore, a 50% lower dose of TGF-b3 used in the Phase III clinical trial as compared with the Phase I/II clinical trials. 166 Antisense oligonucleotides. Antisense oligonucleotides are single-stranded DNA or RNA that are complementary to a specific mRNA sequence which blocks target gene expression either by inhibiting RNA translation or by promoting enzymatic degradation of the mRNA target.…”
Section: Strategies Used For Targeting the Tgf-b Signaling Pathway Tomentioning
confidence: 99%